(untitled) (Tanzania Medical Journal, 2023)
Background Methanol poisoning is a life threatening event with high mortality and morbidity rates. Optic nerve atrophy is one of the commonest morbidity causing irreversible blindness. The case is presented to show how the intoxication can lead to optic atrophy with glaucomatous optic disc damage which is uncommon in most of the reported incidences in Tanzania Case report A 21 years old man reported with a year old history of acute visual loss in both eyes immediately after drinking about 10mls of laboratory methanol during class training session. Day one post incidence he had hand movement vision that slowly progressed to no light perception on arrival at CCBRT. Examination of his intraocular pressure found to be 15 and 14 mmHg in the right and left eye respectively; neither had he had glaucoma before nor using any ant glaucoma drugs. His anterior segment examination revealed normal cornea thickness and angles status. Dilated fundus examination with 90D lens showed bilateral compete Optic nerve pallor with vertical cup to disc ratio (CDR) above 0.9. Systemic evaluation could not find abnormalities. Optical coherence tomography (OCT) for the retina and optic nerve found severe glaucomatous disc damage and loss of Retina nerve fiber layer (RNFL) in keeping with both optic atrophy and end stage glaucoma. He was therefore counselled on irreversible nature of the visual loss and started on visual rehabilitation sessions. Conclusion Methanol poisoning may induce glaucomatous disc cupping in the late stages as well as optic atrophy. This reports a rare evidence of methanol induced optic atrophy with bilateral glaucomatous disc cupping in Tanzania that causes irreversible visual loss and calls for careful handling of the solvent in homes, school laboratories and industries.